Education and Implementation in Handling and Preventing Stunting - Nurhanifah, Dewi; Bianka, Astina; Natasya, Diva Ayu; Syahril, Muhammad; Sabil, Siti Elsa; Putri, Septia Maharani; Khairilatilfa, Saida (UrbanGreen Central Media, 2024)
Various educational programs are being conducted among children and youth in South Alalak, Indonesia to improve health and hygiene. Key initiatives include education on proper handwashing, reproductive health awareness, risks of free association, and stunting prevention. awareness, risks of free association, and stunting prevention. Stunting is a condition where children under five have poor nutrition, resulting in stunted development and resulting in stunted growth and development and making the child too short, underweight, and lacking upper arm circumference. Stunting, which results from chronic malnutrition, has serious long-term consequences, including cognitive decline and increased vulnerability to disease. increased susceptibility to disease. Through interventions that include nutrition counseling, health education sessions, and promotion of hygiene practices, results show that education efforts and nutritious food programs can effectively reduce stunting rates and improve child health. This concludes with a call for continued efforts in health education and prevention strategies to improve well-being. health education and prevention strategies to improve the region's well-being of children and adolescents. This journal aims to reduce stunting rates and improve the well-being of children and adolescents in the region through health education and prevention strategies.